resolva a inequancao do 2°grau (3x-1)(x+1)=0
guilhermemartins143:
sim
Soluções para a tarefa
Respondido por
2
Resposta:
(3x-1)(x+1)=0
3x²+3x-x-1=0
3x²+2x-1=0
Explicação passo-a-passo:
3x² + 3x -x - 1 ≥ 0
3x² + 2x - 1 ≥ 0
se for preciso resolver essa inequação que se formou.
Δ= 4 - 4.3.-1
Δ= 4 + 12
Δ= 16
-b±√Δ÷2a
-2 ± √16 ÷2.3
-2 ± 4 ÷ 6
-2 + 4 ÷6 = 2 ÷6 = 1/3 ou 0,33333
-2-4÷6 = -6÷6 = -1
Perguntas interessantes
História,
9 meses atrás
História,
9 meses atrás
Biologia,
9 meses atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás